The Pathogenicity of Anti-β2GP1-IgG Autoantibodies Depends on Fc Glycosylation - Christoph Fickentscher; Iryna Magorivska; Christina Janko; Mona Biermann; Rostyslav Bilyy; Cecilia Nalli; Angela Tincani; Veronica Medeghini; Antonella Meini; Falk Nimmerjahn; Georg Schett; Luis E. Muñoz; et al. (Journal of Immunology Research)
To analyze the glycosylation of anti-β2GP1, we investigated purified IgG from healthy children, patients with APS, and asymptomatic adult carriers of antiphospholipid antibodies. We observed that in the sera of healthy children and of patients with APS, IgG3 and IgG2 were predominant, respectively. The potentially protective anti-β2GP1-IgM was lower in the sera of healthy children. Although anti-β2GP1-associated C1q did not differ between children and patients with antiphospholipid syndrome, the associated C3c was significantly higher in the sera of healthy children. This indicates a more efficient clearance of anti-β2GP1 immune complexes in the healthy children. This clearance is not accompanied by inflammation or coagulatory events. It is likely that the most important pathogenic factor of the anti-β2GP1-IgG is related to the different glycosylation observed in healthy and diseased individuals. We detected a significantly higher sialylation of anti-β2GP1-IgG isolated from the sera of healthy children and asymptomatic adults when compared with that of patients with clinically apparent antiphospholipid syndrome. Low sialylated IgG reportedly ameliorates inflammation and inflammation promotes hyposialylation. Thus, both reactions create a vicious circle that precipitates the pathology of the antiphospholipid syndrome including thrombus-formation. We conclude that the increased sialylation of anti-β2GP1-IgG of sera of healthy individuals limits their pathogenicity.